Save the doctor and the nurse - Ghiya, Murtuza (Research and Humanities in Medical Education, 2020)
COVID-19 has exposed the weakness in a largely privatized, profit driven health-care business, soaked neck deep in corruption both within and without the so called noble health care system. This is likely to have stemmed from years of under-funding of health care (% GDP spent on health care makes India rank one of the lowest in the world). Although there are a few unscrupulous, unethical black sheep within the medical community, there are many who have dedicated themselves to serve patients with their heart and soul. Some form of media have been consistently sensationalizing and exaggerating physician errors and corruption while not throwing light upon the systemic errors that have lead to business men who make the big bucks in private health care while the doctor is made the face of it!